Investigation of MLH1, MGMT, CDKN2A, and RASSF1A Gene Methylation in Thymomas From Patients With Myasthenia Gravis - Coppedè, Fabio; Ricciardi, Roberta; Lopomo, Angela; Stoccoro, Andrea; De Rosa, Anna; Guida, Melania; Petrucci, Loredana; Maestri, Michelangelo; Lucchi, Marco; Migliore, Lucia (Frontiers in Molecular Neuroscience, 2020)
A feature of thymomas is their frequent association with Myasthenia Gravis (MG), an autoimmune disease characterized by the production of autoantibodies directed to different targets at the neuromuscular junction. Indeed, almost 30-40% of thymomas are found in patients with a type of MG termed thymoma-associated MG (TAMG). Recent studies suggest that TAMG-associated thymomas could represent a molecularly distinct subtype of thymic epithelial tumors (TETs), but few data are still available concerning the epigenetic modifications occurring in TAMG tissues. The promoter methylation levels of DNA repair (MLH1 and MGMT) and tumor suppressor genes (CDKN2A and RASSF1A) have been frequently investigated in TETs, but methylation data in TAMG tissues are scarce and controversial. To further address this issue we investigated MLH1, MGMT, CDKN2A, and RASSF1A methylation levels in blood samples and surgically resected thymomas from 69 TAMG patients, and in the adjacent normal thymus available from 44 of them. Promoter methylation levels of MLH1, MGMT, CDKN2A and RASSF1A genes were not increased in cancer with respect to healthy tissues and did not correlate with the histological or pathological features of the tumor or with the MG symptoms. The present study suggests that hypermethylation of these genes is not frequent in TAMG tissues.